Composite material for coating-free one-time molded photovoltaic bracket bridge and application thereof

By preparing a composite material containing toughened modified tetrafluorophenyl epoxy resin, polybutylene terephthalate, light calcium carbonate, modified layered nickel silicate and modified glass fiber, the traditional metal photovoltaic bracket is easily corrosive, heavy weight, and difficult transportation and construction in outdoors, achieving high mechanical properties, weather resistance, corrosion resistance and high impact toughness.

CN119842183AActive Publication Date: 2025-04-18JIANGXI LONGZHENG TECH DEV CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411962371.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Traditional metal photovoltaic brackets are prone to corrosion, heavy weight, difficult transportation and construction, thermal conductivity leads to components aging and frequent maintenance and coating in outdoor environments, which violates the concept of green energy development.

Method used

The finished pellets were prepared by melt blending, extrusion and granulation using a composite material of 40-50 parts by weight of toughening modified tetrafluorophenyl epoxy resin blend, 10-20 parts by weight of polybutylene terephthalate, 2-3 parts by weight of light calcium carbonate, 4-5 parts by weight of modified phosphorus-containing layered nickel silicate, 3-5 parts by weight of modified glass fiber, 1-2 parts by weight of antioxidant, 0.5-1 parts by weight of ultraviolet stabilizer, 1-2 parts by weight of lubricant and 5-8 parts by weight of curing accelerator.

Benefits of technology

The composite material exhibits excellent mechanical properties, weathering and corrosion resistance and high impact toughness, which can maintain performance in harsh environments, reduce transportation and construction costs, extend service life, and improve the stability and power generation efficiency of photovoltaic systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842183A_ABST
    Figure CN119842183A_ABST
Patent Text Reader

Abstract

The invention provides a composite material for a coating-free one-time formed photovoltaic support bridge and application of the composite material, and belongs to the technical field of preparation of composite materials of photovoltaic support bridges. The preparation process comprises the following steps: preparing a toughened and modified tetrafluorophenyl epoxy resin blend; preparing polyimide containing a trifluoromethyl group; preparing modified glass fibers; preparing phosphorus-containing layered nickel silicate; preparing modified phosphorus-containing layered nickel silicate; and preparing the composite material. According to the invention, tetrafluorophenyl epoxy resin is prepared, polypropylene glycol diglycidyl ether and polyethersulfone are adopted for toughening modification, and then the modified tetrafluorophenyl epoxy resin and polyethersulfone are compounded with various materials such as modified glass fiber and glycidyl ether oxypropyl polysilsesquioxane modified phosphorus-containing layered nickel silicate to prepare the composite material, so that the rigidity is improved, and the toughness of the material is considered; and the mechanical properties of the composite material are more balanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation of photovoltaic support bridge frames, and in particular to a composite material for painting-free one-time forming photovoltaic support bridge frames and applications thereof. Background Art

[0002] As the global energy transition accelerates towards renewable energy, solar photovoltaic power generation has become a key force in the energy field with its outstanding advantages of cleanliness and sustainability, and its installed capacity has shown explosive growth. Photovoltaic bracket bridges are basic structural components that support photovoltaic components and ensure safe and orderly electrical wiring in photovoltaic power stations. They play a vital role in the stability, durability and power generation efficiency of the entire photovoltaic system. Their performance is directly related to the full life cycle benefits of photovoltaic power stations.

[0003] Traditional photovoltaic bracket bridges are mostly made of metal materials, with steel being the most common. Steel is widely available and its initial mechanical strength can still meet the basic load-bearing requirements, but its inherent fatal weaknesses seriously restrict its long-term and efficient application in the photovoltaic industry. On the one hand, metal is extremely susceptible to corrosion. In the complex and changeable outdoor climate environment, whether it is water vapor in humid air, acidic rainfall in industrial areas, or salt-rich sea breeze erosion in coastal areas, the surface of steel quickly oxidizes and rusts, causing the structural strength to drop drastically, which not only greatly reduces the service life, but also makes frequent maintenance and painting a heavy burden. Every few years, a lot of manpower, material resources, and financial resources are required for rust removal and painting operations. The operation and maintenance costs remain high, and the painting process is easy to pollute the surrounding environment, which is contrary to the concept of green energy development.

[0004] On the other hand, the high density of metal materials determines their considerable weight. The transportation process increases vehicle fuel consumption, increases transportation frequency, and raises transportation costs. The handling and installation at the construction site require the assistance of large-scale lifting equipment, which increases the difficulty of construction, prolongs the construction period, and indirectly increases the total cost of the project. It may also cause the accumulation of precision errors due to inconvenient installation, affecting the overall arrangement of the photovoltaic array and reducing power generation efficiency. Furthermore, the good thermal conductivity of metal becomes a disadvantage under sunlight exposure. The absorbed heat is quickly transferred to the connection of the photovoltaic module, forming a local high-temperature hot spot, accelerating the aging of the module, reducing the photoelectric conversion efficiency, and even causing serious failures such as module burning, threatening the safe and stable operation of the power station.

[0005] With the progress of material science and technology, composite materials have gradually entered the field of vision of photovoltaic equipment manufacturing. Although some of the composite materials currently put into use or in the research and development stage are used to prepare one-time molding photovoltaic bracket bridges without painting, they try to overcome the problems of traditional metals that require frequent maintenance and painting and are too heavy to a certain extent, but they are still in a new dilemma. Conventional composite materials based on ordinary thermosetting resins have better corrosion resistance than metals, but they are brittle and weak in impact resistance after curing. Cracks are easily generated by slight external collision and vibration, and they cannot withstand the mechanical impact toughness required for photovoltaic bracket bridges in extreme weather such as strong winds and hail.

[0006] Therefore, we proposed a composite material for painting-free one-time forming photovoltaic bracket bridge frame and its application, which combines excellent mechanical properties, outstanding weather resistance and corrosion resistance, and high impact toughness. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a composite material for a one-time molding photovoltaic support bridge frame without painting and its application.

[0008] A composite material for a one-time molding photovoltaic bracket bridge frame without painting, the composite material comprising 40-50 parts by weight of a toughened modified tetrafluorophenyl epoxy resin blend, 10-20 parts by weight of polybutylene terephthalate, 2-3 parts by weight of light calcium carbonate, 4-5 parts by weight of modified phosphorus-containing layered nickel silicate, 3-5 parts by weight of modified glass fiber, 1-2 parts by weight of an antioxidant, 0.5-1 parts by weight of an ultraviolet stabilizer, 1-2 parts by weight of a lubricant, and 5-8 parts by weight of a curing accelerator;

[0009] The preparation process of the composite material is as follows:

[0010] S1: Preparation of toughened modified tetrafluorophenyl epoxy resin blend, using 2,3,5,6-tetrafluorophenylene glycol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide as raw materials to synthesize tetrafluorophenyl epoxy resin, and then using polypropylene glycol diglycidyl ether and polyether sulfone to modify the tetrafluorophenyl epoxy resin to obtain a toughened modified tetrafluorophenyl epoxy resin blend;

[0011] S2: Preparation of polyimide containing trifluoromethyl group, using hydroquinone and 2-chloro-5-nitrotrifluorotoluene as raw materials to react to obtain intermediate product I, intermediate product I is reduced by iron powder, then ammonium hydroxide is added to prepare intermediate product II, and finally the polyimide containing trifluoromethyl group is prepared by reacting intermediate product II, 4-4-biphenyl ether dianhydride, triethylamine and acetic anhydride;

[0012] S3: Preparation of modified glass fiber, using dopamine to modify the glass fiber and then using a polyimide containing a trifluoromethyl group to modify it to obtain the modified glass fiber;

[0013] S4: Preparation of phosphorus-containing layered nickel silicate: mixing silane coupling agent KH560, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and triphenylphosphine to obtain an intermediate, and reacting the intermediate with nickel chloride hexahydrate to obtain phosphorus-containing layered nickel silicate;

[0014] S5: preparation of modified phosphorus-containing layered nickel silicate, using glycidyl ether oxypropyl polysilsesquioxane to modify the phosphorus-containing layered nickel silicate to obtain modified phosphorus-containing layered nickel silicate;

[0015] S6: Preparation of composite materials: mixing various raw materials, melt blending, extruding, and granulating to obtain finished granules, which are composite materials.

[0016] Furthermore, step S1 of preparing the toughened and modified tetrafluorophenyl epoxy resin blend specifically comprises the following steps:

[0017] S1.1: 1-2 parts by weight of 2,3,5,6-tetrafluorophenylenedimethanol, 2-3 parts by weight of epichlorohydrin and 0.5-1 parts by weight of sodium hydroxide are mechanically stirred and mixed at room temperature for 20-30 minutes, then 0.05-0.1 parts by weight of tetramethylammonium bromide are added, and the mixture is reacted at 67-70°C for 2-3 hours. After the reaction is completed, the mixture is cooled to room temperature and washed with deionized water until the pH value of the aqueous phase is neutral to obtain a tetrafluorophenyl epoxy resin;

[0018] S1.2: Place 80-100 parts by weight of tetrafluorophenyl epoxy resin in an oil bath at 150-180°C, and stir continuously at 200-300 r / min for 10-12 hours to obtain a transparent liquid, then add 30-35 parts by weight of 4,4'-diaminodiphenyl sulfone, and stir continuously at 200-300 r / min to completely dissolve 4,4'-diaminodiphenyl sulfone to obtain a mixture;

[0019] S1.3: Then, 20-25 parts by weight of polypropylene glycol diglycidyl ether and 10-12 parts by weight of polyether sulfone are added to the mixture, and the mixture is blended using a high-speed homogenizer. After the mixture is evenly mixed, the mixture is placed in a vacuum oven preheated to 70-80° C. for degassing for 20-30 minutes to obtain a toughened modified tetrafluorophenyl epoxy resin blend.

[0020] Furthermore, step S2 of preparing the polyimide containing trifluoromethyl groups specifically comprises the following steps:

[0021] S2.1: 2-3 parts by weight of hydroquinone and 3-5 parts by weight of 2-chloro-5-nitrotrifluorotoluene are added to 300-400 parts by weight of NN dimethylacetamide solution, and the mixture is stirred at room temperature for 20-30 minutes. Then, 1-2 parts by weight of anhydrous potassium carbonate are added, and the mixture is stirred and heated at 200-300 r / min and 130-135° C. for 4-5 hours to obtain a reaction system. The reaction system is poured into 500-800 parts by weight of deionized water to obtain a precipitate. The precipitate is rinsed again with deionized water for 2-3 times, and then vacuum dried to obtain an intermediate product I.

[0022] S2.2: After mixing the intermediate product I with 10-20 parts by weight of iron powder, add 30-40 parts by weight of ethanol, stir and mix at 200-300r / min, then add 10-12 parts by weight of 20-30wt% hydrochloric acid solution, stir the mixed system under condensation reflux for 2-3h, add 8-10 parts by weight of 8-10wt% ammonium hydroxide solution within 20-30min of condensation reflux, after the reaction is completed, obtain a precipitate, vacuum filter the precipitate and dry it to obtain an intermediate product II;

[0023] S2.3: Mix 2-3 parts by weight of intermediate product II, 1-2 parts by weight of 4-4-biphenyl ether dianhydride and 200-300 parts by weight of NN dimethylacetamide, stir at 500-600r / min for 4-5h, then add 2-3 parts by weight of triethylamine and 1-2 parts by weight of acetic anhydride, and then heat at 120-130°C for 8-10h. After the reaction is completed, stop heating, filter, and then wash the precipitate with ethanol 2-3 times. Put the washed precipitate into an oven and dry it to obtain a polyimide containing a trifluoromethyl group.

[0024] Furthermore, step S3 of preparing the modified glass fiber specifically comprises the following steps:

[0025] S3.1: Immerse the glass fiber in acetone and ultrasonically clean it for 2-3 times, each time for 20-30 minutes, and then clean the cleaned glass fiber again with distilled water for 2-3 times and then put it into an oven for drying to obtain cleaned glass fiber;

[0026] S3.2: Prepare a 2-3 g / L dopamine solution using dopamine hydrochloride and distilled water, add Tris to adjust the pH value, and test with a pH meter until the pH value reaches 8.5 to obtain a dopamine solution;

[0027] S3.3: Soak the cleaned glass fiber in 20-30 parts by weight of dopamine solution and stir it under magnetic stirring for 4-5 hours, then add 15-20 parts by weight of polyimide containing trifluoromethyl group and stir the mixture at 30-32°C for 8-10 hours, wash the reacted glass fiber with deionized water for 2-3 times and dry it to obtain modified glass fiber.

[0028] Furthermore, step S4 of preparing phosphorus-containing layered nickel silicate specifically comprises the following steps:

[0029] S4.1: Under nitrogen protection, 4-5 parts by weight of silane coupling agent KH560, 3-4 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.3-0.5 parts by weight of triphenylphosphine are mixed, and the mixture is reacted at 130-140° C. for 7-8 hours, and then the solid obtained by the reaction is dried at 70-80° C. to constant weight to obtain an intermediate;

[0030] S4.2: Add 2-3 parts by weight of the intermediate and 0.9-1.2 parts by weight of nickel chloride hexahydrate to 100-120 parts by weight of methanol, stir at 200-300 r / min for 20-30 min to obtain a mixed solution, add the mixed solution to 200-230 parts by weight of a 0.05 mol / L aqueous sodium hydroxide solution, react at room temperature for 3-4 days, then centrifuge, wash and dry to obtain phosphorus-containing layered nickel silicate.

[0031] Furthermore, step S5 of preparing the modified phosphorus-containing layered nickel silicate specifically comprises the following steps:

[0032] S5.1: 3-5 parts by weight of phosphorus-containing layered nickel silicate are added to 10-12 parts by weight of N,N-dimethylformamide, followed by stirring at 200-300 r / min for 20-30 min, ultrasonically dispersing for 20-30 min to obtain a suspension, adding 1-2 parts by weight of glycidyloxypropyl polysilsesquioxane to the suspension, and continuing ultrasonic stirring for 20-30 min to obtain a mixed solution;

[0033] S5.2: The mixed solution is transferred to a reactor and reacted for 10-12 hours under a nitrogen atmosphere at 120-150°C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged, washed and dried to obtain modified phosphorus-containing layered nickel silicate.

[0034] Furthermore, step S6 of preparing the composite material specifically comprises the following steps:

[0035] S6.1: premix 40-50 parts by weight of a toughened modified tetrafluorophenyl epoxy resin blend, 10-20 parts by weight of polybutylene terephthalate, 1-2 parts by weight of an antioxidant, 0.5-1 parts by weight of an ultraviolet stabilizer UV-328, 1-2 parts by weight of zinc stearate and 5-8 parts by weight of a curing accelerator DMP-30 in a mixer at 200-300 r / min for 3-5 minutes at a temperature of 70-90° C. to obtain a mixed resin;

[0036] S6.2: Slowly add 2-3 parts by weight of light calcium carbonate and 4-5 parts by weight of modified phosphorus-containing layered nickel silicate to the mixed resin, stir at 800-1000r / min for 8-12min, and then feed 3-5 parts by weight of modified glass fiber into a twin-screw extruder through a special side feeding device at a uniform speed, with a screw speed of 250-350rpm and a temperature controlled at 230-280°C. After melt blending, extrusion and granulation, finished pellets are obtained, which is a composite material.

[0037] Furthermore, the antioxidant in step S6.1 is antioxidant 1010.

[0038] Furthermore, in step S6.1, the ultraviolet stabilizer is UV-328.

[0039] Application of any of the composite materials described in the invention in a one-time photovoltaic bracket bridge frame that is free of painting.

[0040] Compared with the prior art, the present invention has at least the following beneficial effects:

[0041] 1. The present invention prepares tetrafluorophenyl epoxy resin, introduces tetrafluorophenyl group, and due to the CF bond, unique electronic effect and rich intermolecular force of tetrafluorophenyl, tetrafluorophenyl epoxy resin simultaneously exhibits excellent thermomechanical properties, thermal stability and hydrophobicity. The fluorine element in tetrafluorophenyl epoxy resin has strong electronegativity, so that the molecular chain has low surface energy and high chemical stability, so that the composite material has good tolerance to chemical media such as acid, alkali and salt, and can maintain good performance in harsh chemical environment. In addition, polypropylene glycol diglycidyl ether and polyether sulfone are used for toughening modification, and the glycidyl ether groups at both ends of polypropylene glycol diglycidyl ether can react with tetrafluoro The epoxy groups in the phenyl epoxy resin undergo a ring-opening reaction to form a cross-linked network, and the polypropylene glycol diglycidyl ether has a flexible polyether segment, which can form a flexible phase in the tetrafluorophenyl epoxy resin, absorb and dissipate external energy, and prevent the expansion of cracks, thereby significantly improving the impact resistance of the composite material. Polyether sulfone is a thermoplastic resin and is incompatible with thermosetting epoxy resin. As the curing reaction proceeds, the molecular weight of the epoxy resin continues to increase, and the polyether sulfone will gradually precipitate and exist in the form of a second phase. When the composite material yields and cracks under external force, the polyether sulfone particles will connect the cracks in the form of bridges to prevent further propagation of the cracks, thereby improving the toughness of the composite material.

[0042] 2. In the present invention, dopamine is polymerized on the surface of glass fiber to form a polydopamine coating, which is then modified by a polyimide containing a trifluoromethyl group. The polydopamine coating formed by the polymerization of dopamine on the surface of glass fiber has abundant active functional groups, which can react chemically with the polyimide containing a trifluoromethyl group to form a strong chemical bond connection. The molecular structure of the polyimide containing a trifluoromethyl group has both rigidity and certain flexibility. The rigid part can form a certain mutual support with the rigid structure of the epoxy resin. At the same time, the flexible chain segment helps to alleviate the steric hindrance caused by the collision of the rigid structure, so that the polyimide molecules containing the trifluoromethyl group can be more The modified glass fiber can be well interspersed between the epoxy resin molecules, so that the modified glass fiber can be evenly dispersed between the epoxy resin molecules. When the composite material is subjected to a tensile load, the modified glass fiber acts as a solid pillar, working with the epoxy resin to bear the external force together, thereby significantly improving the tensile strength and modulus of the composite material, making it have a stronger bearing capacity, and the interaction between the polydopamine wrapping layer and the polyimide containing trifluoromethyl groups can effectively absorb and dissipate impact energy; at the same time, the stable interface bonding can ensure that the modified glass fiber will not be easily peeled off from the matrix when subjected to impact, which greatly improves the impact resistance of the composite material, making it show stronger toughness and stability when facing sudden impact.

[0043] 3. The present invention adopts glycidyloxypropyl polysilsesquioxane to modify phosphorus-containing layered nickel silicate. Phosphorus-containing layered nickel silicate itself contains phosphorus element. Phosphorus can form phosphoric acid substances at high temperature. These substances can form a dense protective film on the surface of the material, isolate oxygen, prevent the further spread of flames, and play a role in gas phase flame retardancy. At the same time, the structure of layered nickel silicate can hinder the transfer of heat to a certain extent, delay the thermal decomposition rate of the material, and enhance the flame retardant effect from the solid phase level. The layered nickel silicate contains PH groups that can undergo ring-opening reaction with the epoxy bonds in glycidyloxypropyl polysilsesquioxane to achieve modification, and glycidyloxypropyl polysilsesquioxane contains reactive epoxy groups that can be well combined with the epoxy resin matrix. Its silicon oxygen skeleton structure has high thermal stability, and at high temperature, it is not only difficult to burn itself, but also can further promote the protective film formed by phosphorus-containing layered nickel silicate to be more dense and stable. The synergistic effect of the two greatly improves the flame retardant properties of the composite material. Although the phosphorus-containing layered nickel silicate has strong rigidity, the flexible silicon oxygen chain segments of glycidyloxypropyl polysilsesquioxane can relieve stress concentration to a certain extent and absorb impact energy. When the composite material is impacted by external force, these flexible segments can deform to prevent the rapid expansion of cracks, thereby improving the rigidity while taking into account the toughness of the material, making the mechanical properties of the composite material more balanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0045] Figure 1 This is a process flow chart of a composite material for a one-time molding photovoltaic bracket bridge frame without painting adopted in an embodiment of the present invention. DETAILED DESCRIPTION

[0046] The composite material for the one-time forming photovoltaic bracket bridge frame without painting provided by the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0047] Infrared and NMR data:

[0048] Tetrafluorophenyl epoxy resin:

[0049] FTIR(KBr,cm -1 ):3300-3600(-OH),1286(CF),and903(epoxygroup). 1 HNM R(400MHz, CDCl3, ppm) δ4.70(qt,2H),3.83(dd,1H),3.47(dd,1H),3.17(ddt,1H),2.81(dd,1H),2.63(dd,1H). 13 CNMR(101MHz, CDCl3, ppm)*δ146.25,143.86,116.31,71.45,60.33,50.55,44.08.

[0050] Reaction process and structure of polyimide containing trifluoromethyl group:

[0051]

[0052] Phosphorus-containing layered nickel silicate structure:

[0053]

[0054] Example 1

[0055] Preparation process of composite materials for one-time molding of photovoltaic bracket bridge without painting, such as Figure 1 As shown, the following steps are included:

[0056] S1: Preparation of toughened modified tetrafluorophenyl epoxy resin blends

[0057] S1.1: 1 part by weight of 2,3,5,6-tetrafluorophenylenedimethanol, 2 parts by weight of epichlorohydrin and 0.5 parts by weight of sodium hydroxide were mechanically stirred and mixed at room temperature for 20 minutes, then 0.05 parts by weight of tetramethylammonium bromide was added, and the mixture was reacted at 67°C for 2 hours. After the reaction was completed, the mixture was cooled to room temperature and washed with deionized water until the pH value of the aqueous phase was neutral, thereby obtaining a tetrafluorophenyl epoxy resin;

[0058] S1.2: 80 parts by weight of tetrafluorophenyl epoxy resin were placed in an oil bath at 150°C, and stirred continuously at 200 r / min for 10 hours to obtain a transparent liquid, and then 30 parts by weight of 4,4'-diaminodiphenyl sulfone were added, and stirred continuously at 200 r / min to completely dissolve the 4,4'-diaminodiphenyl sulfone to obtain a mixture;

[0059] S1.3: Then, 20 parts by weight of polypropylene glycol diglycidyl ether and 10 parts by weight of polyether sulfone are added to the mixture, and the mixture is blended using a high-speed homogenizer. After the mixture is evenly mixed, the mixture is placed in a vacuum oven preheated to 70° C. for 20 minutes for degassing to obtain a toughened modified tetrafluorophenyl epoxy resin blend;

[0060] S2: Preparation of polyimide containing trifluoromethyl groups

[0061] S2.1: 2 parts by weight of hydroquinone and 3 parts by weight of 2-chloro-5-nitrotrifluorotoluene are added to 300 parts by weight of NN dimethylacetamide solution, and the mixture is stirred at room temperature for 20 minutes. Then, 1 part by weight of anhydrous potassium carbonate is added, and the mixture is stirred and heated at 200 r / min and 130° C. for 4 hours to obtain a reaction system. The reaction system is poured into 500 parts by weight of deionized water to obtain a precipitate. The precipitate is rinsed with deionized water twice again, and then vacuum dried to obtain an intermediate product I.

[0062] S2.2: After mixing the intermediate product I with 10 parts by weight of iron powder, 30 parts by weight of ethanol were added, and the mixture was stirred at 200 r / min, and then 10 parts by weight of 20wt% hydrochloric acid solution were added, and the mixture was stirred for 2h under condensation reflux, and 8 parts by weight of 8wt% ammonium hydroxide solution were added within 20min of condensation reflux. After the reaction was completed, a precipitate was obtained, and the precipitate was vacuum filtered and dried to obtain an intermediate product II;

[0063] S2.3: 2 parts by weight of intermediate product II, 1 part by weight of 4-4 biphenyl ether dianhydride and 200 parts by weight of NN dimethylacetamide were mixed, stirred at 500 r / min for 4 hours, then 2 parts by weight of triethylamine and 1 part by weight of acetic anhydride were added, and then heated at 120°C for 8 hours. After the reaction was completed, heating was stopped, filtered, and then the precipitate was washed twice with ethanol, and the washed precipitate was placed in an oven and dried to obtain a polyimide containing a trifluoromethyl group;

[0064] S3: Preparation of modified glass fiber

[0065] S3.1: The glass fiber is immersed in acetone and ultrasonically cleaned twice, each time for 20 minutes, and the cleaned glass fiber is washed again twice with distilled water and then placed in an oven for drying to obtain a cleaned glass fiber;

[0066] S3.2: Prepare a 2 g / L dopamine solution using dopamine hydrochloride and distilled water, add Tris to adjust the pH value, and test with a pH meter until the pH value reaches 8.5 to obtain a dopamine solution;

[0067] S3.3: Soaking the cleaned glass fiber in 20 parts by weight of a dopamine solution and stirring it under magnetic stirring for 4 hours, then adding 15 parts by weight of a polyimide containing a trifluoromethyl group and stirring and reacting it at 30° C. for 8 hours, washing the reacted glass fiber twice with deionized water and drying it to obtain a modified glass fiber;

[0068] S4: Preparation of phosphorus-containing layered nickel silicate

[0069] S4.1: Under nitrogen protection, 4 parts by weight of silane coupling agent KH560, 3 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.3 parts by weight of triphenylphosphine were mixed, and reacted at 130° C. for 7 h, and then the solid obtained by the reaction was dried at 70° C. to constant weight to obtain an intermediate;

[0070] S4.2: Add 2 parts by weight of the intermediate and 0.9 parts by weight of nickel chloride hexahydrate to 100 parts by weight of methanol, stir at 200 r / min for 20 min to obtain a mixed solution, add the mixed solution to 200 parts by weight of a 0.05 mol / L sodium hydroxide aqueous solution, react at room temperature for 3 days, then centrifuge, wash and dry to obtain phosphorus-containing layered nickel silicate;

[0071] S5: Preparation of modified phosphorus-containing layered nickel silicate

[0072] S5.1: 3 parts by weight of phosphorus-containing layered nickel silicate are added to 10 parts by weight of N,N-dimethylformamide, followed by stirring at 200 r / min for 20 minutes, ultrasonically dispersed for 20 minutes to obtain a suspension, 1 part by weight of glycidyloxypropyl polysilsesquioxane is added to the suspension, and ultrasonic stirring is continued for 20 minutes to obtain a mixed solution;

[0073] S5.2: The mixed solution is transferred to a reactor, and the reaction is carried out under a nitrogen atmosphere at 120° C. for 10 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, washed and dried to obtain a modified phosphorus-containing layered nickel silicate;

[0074] S6: Preparation of composite materials

[0075] S6.1: 40 parts by weight of toughened modified tetrafluorophenyl epoxy resin blend, 10 parts by weight of polybutylene terephthalate, 1 part by weight of antioxidant 1010, 0.5 parts by weight of UV stabilizer UV-328, 1 part by weight of zinc stearate and 5 parts by weight of curing accelerator DMP-30 were premixed in a mixer at 200 r / min for 3 min at a temperature of 70° C. to obtain a mixed resin;

[0076] S6.2: Slowly add 2 parts by weight of light calcium carbonate and 4 parts by weight of modified phosphorus-containing layered nickel silicate into the mixed resin, stir at 800r / min for 8 minutes, and then feed 3 parts by weight of modified glass fiber into a twin-screw extruder through a special side feeding device at a uniform speed. The screw speed is 250rpm and the temperature is controlled at 230°C. After melt blending, extrusion and granulation, finished pellets are obtained, which is a composite material.

[0077] Example 2

[0078] Preparation process of composite materials for one-time molding of photovoltaic bracket bridge without painting, such as Figure 1 As shown, the following steps are included:

[0079] S1: Preparation of toughened modified tetrafluorophenyl epoxy resin blends

[0080] S1.1: 2 parts by weight of 2,3,5,6-tetrafluorophenylenedimethanol, 3 parts by weight of epichlorohydrin and 1 part by weight of sodium hydroxide were mechanically stirred and mixed at room temperature for 20 minutes, and then 0.1 parts by weight of tetramethylammonium bromide was added and reacted at 67°C for 2 hours. After the reaction was completed, the mixture was cooled to room temperature and washed with deionized water until the pH value of the aqueous phase was neutral to obtain a tetrafluorophenyl epoxy resin;

[0081] S1.2: 100 parts by weight of tetrafluorophenyl epoxy resin was placed in an oil bath at 150°C, and stirred continuously at 200 r / min for 10 hours to obtain a transparent liquid, and then 35 parts by weight of 4,4'-diaminodiphenyl sulfone was added, and stirred continuously at 200 r / min to completely dissolve 4,4'-diaminodiphenyl sulfone to obtain a mixture;

[0082] S1.3: Then, 25 parts by weight of polypropylene glycol diglycidyl ether and 12 parts by weight of polyether sulfone are added to the mixture, and the mixture is blended using a high-speed homogenizer. After the mixture is evenly mixed, the mixture is placed in a vacuum oven preheated to 70° C. for 20 minutes for degassing to obtain a toughened modified tetrafluorophenyl epoxy resin blend;

[0083] S2: Preparation of polyimide containing trifluoromethyl groups

[0084] S2.1: 3 parts by weight of hydroquinone and 5 parts by weight of 2-chloro-5-nitrotrifluorotoluene are added to 400 parts by weight of NN dimethylacetamide solution, and the mixture is stirred at room temperature for 20 minutes. Then, 2 parts by weight of anhydrous potassium carbonate are added, and the mixture is stirred and heated at 200 r / min and 130° C. for 4 hours to obtain a reaction system. The reaction system is poured into 800 parts by weight of deionized water to obtain a precipitate. The precipitate is rinsed with deionized water twice again, and then vacuum dried to obtain an intermediate product I.

[0085] S2.2: After mixing the intermediate product I with 20 parts by weight of iron powder, 40 parts by weight of ethanol were added, and the mixture was stirred at 200 r / min, and then 12 parts by weight of 30wt% hydrochloric acid solution were added, and the mixture was stirred for 2h under condensation reflux, and 10 parts by weight of 10wt% ammonium hydroxide solution was added within 20min of condensation reflux. After the reaction was completed, a precipitate was obtained, and the precipitate was vacuum filtered and dried to obtain an intermediate product II;

[0086] S2.3: 3 parts by weight of intermediate product II, 2 parts by weight of 4-4 biphenyl ether dianhydride and 300 parts by weight of NN dimethylacetamide were mixed, stirred at 500 r / min for 4 hours, then 3 parts by weight of triethylamine and 2 parts by weight of acetic anhydride were added, and then heated at 120°C for 8 hours. After the reaction was completed, heating was stopped, filtered, and then the precipitate was washed twice with ethanol, and the washed precipitate was placed in an oven and dried to obtain a polyimide containing a trifluoromethyl group;

[0087] S3: Preparation of modified glass fiber

[0088] S3.1: The glass fiber is immersed in acetone and ultrasonically cleaned twice, each time for 20 minutes, and the cleaned glass fiber is washed again twice with distilled water and then placed in an oven for drying to obtain a cleaned glass fiber;

[0089] S3.2: Prepare a 3 g / L dopamine solution using dopamine hydrochloride and distilled water, add Tris to adjust the pH value, and test with a pH meter until the pH value reaches 8.5 to obtain a dopamine solution;

[0090] S3.3: Soaking the cleaned glass fiber in 30 parts by weight of a dopamine solution and stirring it under magnetic stirring for 4 hours, then adding 20 parts by weight of a polyimide containing a trifluoromethyl group and stirring and reacting it at 30° C. for 8 hours, washing the reacted glass fiber twice with deionized water and drying it to obtain a modified glass fiber;

[0091] S4: Preparation of phosphorus-containing layered nickel silicate

[0092] S4.1: Under nitrogen protection, 5 parts by weight of silane coupling agent KH560, 4 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.5 parts by weight of triphenylphosphine were mixed, and reacted at 130° C. for 7 hours, and then the solid obtained by the reaction was dried at 70° C. to constant weight to obtain an intermediate;

[0093] S4.2: 3 parts by weight of the intermediate and 1.2 parts by weight of nickel chloride hexahydrate are added to 120 parts by weight of methanol, stirred at 200 r / min for 20 min to obtain a mixed solution, and the mixed solution is added to 230 parts by weight of a 0.05 mol / L sodium hydroxide aqueous solution, reacted at room temperature for 3 days, and then centrifuged, washed and dried to obtain phosphorus-containing layered nickel silicate;

[0094] S5: Preparation of modified phosphorus-containing layered nickel silicate

[0095] S5.1: 5 parts by weight of phosphorus-containing layered nickel silicate are added to 12 parts by weight of N,N-dimethylformamide, followed by stirring at 200 r / min for 20 minutes, ultrasonically dispersed for 20 minutes to obtain a suspension, 2 parts by weight of glycidyloxypropyl polysilsesquioxane are added to the suspension, and ultrasonic stirring is continued for 20 minutes to obtain a mixed solution;

[0096] S5.2: The mixed solution is transferred to a reactor, and the reaction is carried out under a nitrogen atmosphere at 120° C. for 10 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, washed and dried to obtain a modified phosphorus-containing layered nickel silicate;

[0097] S6: Preparation of composite materials

[0098] S6.1: 50 parts by weight of toughened modified tetrafluorophenyl epoxy resin blend, 20 parts by weight of polybutylene terephthalate, 2 parts by weight of antioxidant 1010, 1 part by weight of UV stabilizer UV-328, 2 parts by weight of zinc stearate and 8 parts by weight of curing accelerator DMP-30 were premixed in a mixer at 200 r / min for 3 min at a temperature of 70° C. to obtain a mixed resin;

[0099] S6.2: Slowly add 3 parts by weight of light calcium carbonate and 5 parts by weight of modified phosphorus-containing layered nickel silicate into the mixed resin, stir at 800r / min for 8 minutes, and then feed 5 parts by weight of modified glass fiber into a twin-screw extruder through a special side feeding device at a uniform speed. The screw speed is 250rpm and the temperature is controlled at 230°C. After melt blending, extrusion and granulation, finished pellets are obtained, which is a composite material.

[0100] Example 3

[0101] Preparation process of composite materials for one-time molding of photovoltaic bracket bridge without painting, such as Figure 1 As shown, the following steps are included:

[0102] S1: Preparation of toughened modified tetrafluorophenyl epoxy resin blends

[0103] S1.1: 1 part by weight of 2,3,5,6-tetrafluorophenylenedimethanol, 2 parts by weight of epichlorohydrin and 0.5 parts by weight of sodium hydroxide were mechanically stirred and mixed at room temperature for 30 minutes, then 0.05 parts by weight of tetramethylammonium bromide was added, and the mixture was reacted at 70°C for 3 hours. After the reaction was completed, the mixture was cooled to room temperature and washed with deionized water until the pH value of the aqueous phase was neutral, thereby obtaining a tetrafluorophenyl epoxy resin;

[0104] S1.2: 80 parts by weight of tetrafluorophenyl epoxy resin were placed in an oil bath at 180°C, and stirred continuously at 300 r / min for 12 hours to obtain a transparent liquid, and then 30 parts by weight of 4,4'-diaminodiphenyl sulfone were added, and stirred continuously at 300 r / min to completely dissolve the 4,4'-diaminodiphenyl sulfone to obtain a mixture;

[0105] S1.3: Then, 20 parts by weight of polypropylene glycol diglycidyl ether and 10 parts by weight of polyether sulfone are added to the mixture, and the mixture is blended using a high-speed homogenizer. After the mixture is evenly mixed, the mixture is placed in a vacuum oven preheated to 80° C. for 30 minutes for degassing to obtain a toughened modified tetrafluorophenyl epoxy resin blend;

[0106] S2: Preparation of polyimide containing trifluoromethyl groups

[0107] S2.1: 2 parts by weight of hydroquinone and 3 parts by weight of 2-chloro-5-nitrotrifluorotoluene are added to 300 parts by weight of NN dimethylacetamide solution, and the mixture is stirred at room temperature for 30 minutes. Then, 1 part by weight of anhydrous potassium carbonate is added, and the mixture is stirred and heated at 300 r / min and 135° C. for 5 hours to obtain a reaction system. The reaction system is poured into 500 parts by weight of deionized water to obtain a precipitate. The precipitate is rinsed with deionized water again for 3 times, and then vacuum dried to obtain an intermediate product I.

[0108] S2.2: After mixing the intermediate product I with 10 parts by weight of iron powder, 30 parts by weight of ethanol were added, and the mixture was stirred at 300 r / min, and then 10 parts by weight of 20wt% hydrochloric acid solution were added, and the mixture was stirred for 3 hours under condensation reflux, and 8 parts by weight of 8wt% ammonium hydroxide solution were added within 30 minutes of condensation reflux. After the reaction was completed, a precipitate was obtained, and the precipitate was vacuum filtered and dried to obtain an intermediate product II;

[0109] S2.3: 2 parts by weight of intermediate product II, 1 part by weight of 4-4 biphenyl ether dianhydride and 200 parts by weight of NN dimethylacetamide were mixed, stirred at 600 r / min for 5 h, then 2 parts by weight of triethylamine and 1 part by weight of acetic anhydride were added, and then heated at 130°C for 10 h. After the reaction was completed, heating was stopped, filtered, and then the precipitate was washed with ethanol for 3 times, and the washed precipitate was placed in an oven and dried to obtain a polyimide containing a trifluoromethyl group;

[0110] S3: Preparation of modified glass fiber

[0111] S3.1: The glass fiber is immersed in acetone and ultrasonically cleaned for 3 times, each time for 30 minutes, and the cleaned glass fiber is washed again for 3 times with distilled water and then placed in an oven for drying to obtain a cleaned glass fiber;

[0112] S3.2: Prepare a 2 g / L dopamine solution using dopamine hydrochloride and distilled water, add Tris to adjust the pH value, and test with a pH meter until the pH value reaches 8.5 to obtain a dopamine solution;

[0113] S3.3: Soaking the cleaned glass fiber in 20 parts by weight of a dopamine solution and stirring it under magnetic stirring for 5 hours, then adding 15 parts by weight of a polyimide containing a trifluoromethyl group and stirring and reacting it at 32° C. for 10 hours, washing the reacted glass fiber with deionized water for 3 times and drying it to obtain a modified glass fiber;

[0114] S4: Preparation of phosphorus-containing layered nickel silicate

[0115] S4.1: Under nitrogen protection, 4 parts by weight of silane coupling agent KH560, 3 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.3 parts by weight of triphenylphosphine were mixed, and reacted at 140° C. for 8 h, and then the solid obtained by the reaction was dried at 80° C. to constant weight to obtain an intermediate;

[0116] S4.2: 2 parts by weight of the intermediate and 0.9 parts by weight of nickel chloride hexahydrate are added to 100 parts by weight of methanol, stirred at 300 r / min for 30 min to obtain a mixed solution, and the mixed solution is added to 200 parts by weight of a 0.05 mol / L sodium hydroxide aqueous solution, reacted at room temperature for 4 days, and then centrifuged, washed and dried to obtain phosphorus-containing layered nickel silicate;

[0117] S5: Preparation of modified phosphorus-containing layered nickel silicate

[0118] S5.1: 3 parts by weight of phosphorus-containing layered nickel silicate are added to 10 parts by weight of N,N-dimethylformamide, followed by stirring at 300 r / min for 30 minutes, ultrasonically dispersed for 30 minutes to obtain a suspension, 1 part by weight of glycidyloxypropyl polysilsesquioxane is added to the suspension, and ultrasonic stirring is continued for 30 minutes to obtain a mixed solution;

[0119] S5.2: The mixed solution is transferred to a reactor, and the reaction is carried out under a nitrogen atmosphere at 150° C. for 12 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, washed and dried to obtain a modified phosphorus-containing layered nickel silicate;

[0120] S6: Preparation of composite materials

[0121] S6.1: 40 parts by weight of toughened modified tetrafluorophenyl epoxy resin blend, 10 parts by weight of polybutylene terephthalate, 1 part by weight of antioxidant 1010, 0.5 parts by weight of UV stabilizer UV-328, 1 part by weight of zinc stearate and 5 parts by weight of curing accelerator DMP-30 were premixed in a mixer at 300 r / min for 5 min at a temperature of 90° C. to obtain a mixed resin;

[0122] S6.2: Slowly add 2 parts by weight of light calcium carbonate and 4 parts by weight of modified phosphorus-containing layered nickel silicate into the mixed resin, stir at 1000r / min for 12 minutes, and then feed 3 parts by weight of modified glass fiber into a twin-screw extruder through a special side feeding device at a uniform speed. The screw speed is 350rpm and the temperature is controlled at 280°C. After melt blending, extrusion and granulation, finished pellets are obtained, which is a composite material.

[0123] Comparative Example 1

[0124] Compared with Example 1, the difference of Comparative Example 1 is that, in Comparative Example 1, polypropylene glycol diglycidyl ether in step S1.3 is removed, and the other steps remain unchanged to prepare the composite material, which is recorded as Comparative Example 1.

[0125] Comparative Example 2

[0126] Compared with Example 1, the difference of Comparative Example 2 is that the polyethersulfone in step S1.3 is removed in Comparative Example 1, and the other steps remain unchanged to prepare the composite material, which is recorded as Comparative Example 2.

[0127] Comparative Example 3

[0128] Compared with Example 1, Comparative Example 3 is different in that, in Comparative Example 3, the polyimide containing trifluoromethyl groups in steps S2 and S3.3 is removed, and the remaining steps remain unchanged to prepare the composite material, which is recorded as Comparative Example 3.

[0129] Comparative Example 4

[0130] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes step S5, replaces the modified phosphorus-containing layered nickel silicate in S6.2 with phosphorus-containing layered nickel silicate, and prepares the composite material without changing the other steps, which is recorded as Comparative Example 4.

[0131] Comparative Example 5

[0132] Compared with Example 1, the difference of Comparative Example 5 is that step S1.1 is removed in Comparative Example 5, the tetrafluorophenyl epoxy resin in S1.2 is replaced by epoxy resin, and the remaining steps remain unchanged to prepare the composite material, which is recorded as Comparative Example 5.

[0133] Comparative Example 6

[0134] Compared with Example 1, the difference of Comparative Example 6 is that Comparative Example 6 removes steps S4 and S5, replaces the modified phosphorus-containing layered nickel silicate in S6.2 with glycidyl ether oxypropyl polysilsesquioxane, and prepares the composite material without changing the other steps, which is recorded as Comparative Example 6.

[0135] The composite materials prepared in Examples 1-3 and Comparative Examples 1-6 are used to prepare disposable photovoltaic bracket bridge frame samples by injection molding or extrusion process for later use.

[0136] The photovoltaic bracket bridge samples prepared in Examples 1-3 were tested for corrosion resistance, bending strength, tensile strength, impact strength and flame retardancy:

[0137] The flexural strength is measured according to GB / T1449-2005, the tensile strength is tested according to GB / T1447-2005, the impact strength is measured according to GB / T1843-2008, and the flame retardancy is measured according to GB / T2408-2021.

[0138] The measurement results are shown in Table 1.

[0139] Table 1. Performance measurement results of Examples 1-3

[0140]

[0141] It can be seen from the data in Table 1 that the composite material prepared by the present invention has excellent mechanical properties and toughness, and can play a good flame retardant effect.

[0142] Corrosion resistance: 5 samples were prepared for each test object, and the contact angle was tested. Then they were immersed in distilled water, 2% sulfuric acid solution, 2% sodium hydroxide solution, 10% sulfuric acid solution and 10% sodium hydroxide solution for 7 days. After being taken out, the contact angle was tested again. The test value after immersion was subtracted from the test value before immersion, and the obtained phase difference was recorded. The degree of corrosion was judged according to the recorded phase difference. The larger the phase difference, the greater the change in contact angle before and after immersion, the more serious the corrosion, and the worse the corrosion resistance of the corresponding sample.

[0143] The corrosion resistance test was performed on Examples 1-3 and Comparative Example 5.

[0144] Please refer to Table 2 for the test results.

[0145] Table 2. Corrosion resistance test results of Examples 1-3

[0146]

[0147] It can be seen from the data in Table 2 that the composite material prepared by the present invention has excellent corrosion resistance.

[0148] It can be seen from the data of Comparative Example 5 that the composite material prepared by using tetrafluorophenyl epoxy resin has good tolerance to chemical media such as acid and alkali, and can improve the corrosion resistance of the composite material.

[0149] The data of Example 1 was used to measure the impact strength of Comparative Examples 1-4. The measurement results are shown in Table 3.

[0150] Table 3. Impact strength test results of Comparative Examples 1-4

[0151] <![CDATA[Impact strength kJ / m 2 > Example 1 39.4 Comparative Example 1 25.4 Comparative Example 2 28.5 Comparative Example 3 24.3 Comparative Example 4 30.1

[0152] It can be seen from the data in Table 3 that the data of Comparative Example 1 and Comparative Example 2 are both smaller than those in Example 1, indicating that the effect of toughening and modifying tetrafluorophenyl epoxy resin with a single component of polypropylene glycol diglycidyl ether or polyether sulfone is not as good as the effect of synergistic toughening and modification with polypropylene glycol diglycidyl ether and polyether sulfone, indicating that the interaction between polypropylene glycol diglycidyl ether and polyether sulfone for toughening and modification significantly improves the toughness of the composite material.

[0153] It can be seen from the data of Comparative Example 3 that the impact strength has decreased, indicating that the glass fiber modified with polyimide of trifluoromethyl group can improve the impact resistance of the composite material, making it show stronger toughness and stability when facing sudden impact.

[0154] It can be seen from the data of Comparative Example 4 that the presence of glycidyloxypropyl polysilsesquioxane can improve the impact resistance of the composite material.

[0155] The data of Example 1 were used to determine the flame retardancy of Comparative Examples 4 and 6.

[0156] The measurement results are shown in Table 4.

[0157] Table 4. Flame retardancy test results of Comparative Examples 4 and 6

[0158]

[0159]

[0160] It can be seen from the data in Table 4 that the flame retardancy of Comparative Examples 4 and 7 is poorer than that of the embodiment, indicating that the synergistic effect of glycidyloxypropyl polysilsesquioxane and phosphorus-containing layered nickel silicate greatly improves the flame retardancy of the composite material.

[0161] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A composite material for a one-time forming photovoltaic bracket bridge frame without painting, characterized in that: The composite material comprises 40-50 parts by weight of a toughened modified tetrafluorophenyl epoxy resin blend, 10-20 parts by weight of polybutylene terephthalate, 2-3 parts by weight of light calcium carbonate, 4-5 parts by weight of modified phosphorus-containing layered nickel silicate, 3-5 parts by weight of modified glass fiber, 1-2 parts by weight of antioxidant, 0.5-1 parts by weight of ultraviolet stabilizer, 1-2 parts by weight of lubricant and 5-8 parts by weight of curing accelerator; The preparation process of the composite material is as follows: S1: Preparation of toughened modified tetrafluorophenyl epoxy resin blend, using 2,3,5,6-tetrafluorophenylene glycol, epichlorohydrin, sodium hydroxide and tetramethylammonium bromide as raw materials to synthesize tetrafluorophenyl epoxy resin, and then using polypropylene glycol diglycidyl ether and polyether sulfone to modify the tetrafluorophenyl epoxy resin to obtain a toughened modified tetrafluorophenyl epoxy resin blend; S2: Preparation of polyimide containing trifluoromethyl group, using hydroquinone and 2-chloro-5-nitrotrifluorotoluene as raw materials to react to obtain intermediate product I, intermediate product I is reduced by iron powder, then ammonium hydroxide is added to prepare intermediate product II, and finally the polyimide containing trifluoromethyl group is prepared by reacting intermediate product II, 4-4-biphenyl ether dianhydride, triethylamine and acetic anhydride; S3: Preparation of modified glass fiber, using dopamine to modify the glass fiber and then using a polyimide containing a trifluoromethyl group to modify it to obtain the modified glass fiber; S4: Preparation of phosphorus-containing layered nickel silicate: mixing silane coupling agent KH560, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and triphenylphosphine to obtain an intermediate, and reacting the intermediate with nickel chloride hexahydrate to obtain phosphorus-containing layered nickel silicate; S5: preparation of modified phosphorus-containing layered nickel silicate, using glycidyl ether oxypropyl polysilsesquioxane to modify the phosphorus-containing layered nickel silicate to obtain modified phosphorus-containing layered nickel silicate; S6: Preparation of composite materials: mixing various raw materials, melt blending, extruding, and granulating to obtain finished granules, which are composite materials.

2. The composite material for the one-time molding of a photovoltaic support bridge without painting according to claim 1, characterized in that: Step S1: Preparation of toughened and modified tetrafluorophenyl epoxy resin blend, specifically comprising the following steps: S1.1: 1-2 parts by weight of 2,3,5,6-tetrafluorophenylenedimethanol, 2-3 parts by weight of epichlorohydrin and 0.5-1 parts by weight of sodium hydroxide are mechanically stirred and mixed at room temperature for 20-30 minutes, then 0.05-0.1 parts by weight of tetramethylammonium bromide are added, and the mixture is reacted at 67-70°C for 2-3 hours. After the reaction is completed, the mixture is cooled to room temperature and washed with deionized water until the pH value of the aqueous phase is neutral to obtain a tetrafluorophenyl epoxy resin; S1.2: Place 80-100 parts by weight of tetrafluorophenyl epoxy resin in an oil bath at 150-180°C, and stir continuously at 200-300 r / min for 10-12 hours to obtain a transparent liquid, then add 30-35 parts by weight of 4,4'-diaminodiphenyl sulfone, and stir continuously at 200-300 r / min to completely dissolve 4,4'-diaminodiphenyl sulfone to obtain a mixture; S1.3: Then, 20-25 parts by weight of polypropylene glycol diglycidyl ether and 10-12 parts by weight of polyether sulfone are added to the mixture, and the mixture is blended using a high-speed homogenizer. After the mixture is evenly mixed, the mixture is placed in a vacuum oven preheated to 70-80° C. for degassing for 20-30 minutes to obtain a toughened modified tetrafluorophenyl epoxy resin blend.

3. The composite material for the one-time molding of a photovoltaic support bridge without painting according to claim 2, characterized in that: Step S2: Preparation of polyimide containing trifluoromethyl group, specifically comprising the following steps: S2.1: 2-3 parts by weight of hydroquinone and 3-5 parts by weight of 2-chloro-5-nitrotrifluorotoluene are added to 300-400 parts by weight of NN dimethylacetamide solution, and the mixture is stirred at room temperature for 20-30 minutes. Then, 1-2 parts by weight of anhydrous potassium carbonate are added, and the mixture is stirred and heated at 200-300 r / min and 130-135° C. for 4-5 hours to obtain a reaction system. The reaction system is poured into 500-800 parts by weight of deionized water to obtain a precipitate. The precipitate is rinsed again with deionized water for 2-3 times, and then vacuum dried to obtain an intermediate product I. S2.2: After mixing the intermediate product I with 10-20 parts by weight of iron powder, add 30-40 parts by weight of ethanol, stir and mix at 200-300r / min, then add 10-12 parts by weight of 20-30wt% hydrochloric acid solution, stir the mixed system under condensation reflux for 2-3h, add 8-10 parts by weight of 8-10wt% ammonium hydroxide solution within 20-30min of condensation reflux, after the reaction is completed, obtain a precipitate, vacuum filter the precipitate and dry it to obtain an intermediate product II; S2.3: Mix 2-3 parts by weight of intermediate product II, 1-2 parts by weight of 4-4-biphenyl ether dianhydride and 200-300 parts by weight of NN dimethylacetamide, stir at 500-600r / min for 4-5h, then add 2-3 parts by weight of triethylamine and 1-2 parts by weight of acetic anhydride, and then heat at 120-130°C for 8-10h. After the reaction is completed, stop heating, filter, and then wash the precipitate with ethanol 2-3 times. Put the washed precipitate into an oven and dry it to obtain a polyimide containing a trifluoromethyl group.

4. The composite material for the one-time molding of a photovoltaic support bridge without painting according to claim 3 is characterized in that: Step S3: Preparation of modified glass fiber, specifically comprising the following steps: S3.1: Immerse the glass fiber in acetone and ultrasonically clean it for 2-3 times, each time for 20-30 minutes, and then clean the cleaned glass fiber again with distilled water for 2-3 times and then put it into an oven for drying to obtain cleaned glass fiber; S3.2: Prepare a 2-3 g / L dopamine solution using dopamine hydrochloride and distilled water, add Tris to adjust the pH value, and test with a pH meter until the pH value reaches 8.5 to obtain a dopamine solution; S3.3: Soak the cleaned glass fiber in 20-30 parts by weight of dopamine solution and stir it under magnetic stirring for 4-5 hours, then add 15-20 parts by weight of polyimide containing trifluoromethyl group and stir the mixture at 30-32°C for 8-10 hours, wash the reacted glass fiber with deionized water for 2-3 times and dry it to obtain modified glass fiber.

5. The composite material for the one-time molding of photovoltaic bracket bridge without painting according to claim 4, characterized in that: Step S4: Preparation of phosphorus-containing layered nickel silicate, specifically comprising the following steps: S4.1: Under nitrogen protection, 4-5 parts by weight of silane coupling agent KH560, 3-4 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.3-0.5 parts by weight of triphenylphosphine are mixed, and the mixture is reacted at 130-140° C. for 7-8 hours, and then the solid obtained by the reaction is dried at 70-80° C. to constant weight to obtain an intermediate; S4.2: Add 2-3 parts by weight of the intermediate and 0.9-1.2 parts by weight of nickel chloride hexahydrate to 100-120 parts by weight of methanol, stir at 200-300 r / min for 20-30 min to obtain a mixed solution, add the mixed solution to 200-230 parts by weight of a 0.05 mol / L aqueous sodium hydroxide solution, react at room temperature for 3-4 days, then centrifuge, wash and dry to obtain phosphorus-containing layered nickel silicate.

6. The composite material for the one-time molding of a photovoltaic support bridge without painting according to claim 5, characterized in that: Step S5: Preparation of modified phosphorus-containing layered nickel silicate, specifically comprising the following steps: S5.1: Add 3-5 parts by weight of phosphorus-containing layered nickel silicate to 10-12 parts by weight of N,N-dimethylformamide, then stir at 200-300 r / min for 20-30 min, ultrasonically disperse for 20-30 min to obtain a suspension, add 1-2 parts by weight of glycidyloxypropyl polysilsesquioxane to the suspension, continue ultrasonic stirring for 20-30 min to obtain a mixed solution; S5.2: Transfer the mixed solution to a reactor, react under a nitrogen atmosphere at 120-150°C for 10-12 h, and after the reaction is completed, cool the reaction product to room temperature, and then centrifuge, wash and dry to obtain modified phosphorus-containing layered nickel silicate.

7. The composite material for the one-time molding of a photovoltaic support bridge frame without painting according to claim 6, characterized in that: Step S6: Preparation of the composite material, specifically comprising the following steps: S6.1: premix 40-50 parts by weight of a toughened modified tetrafluorophenyl epoxy resin blend, 10-20 parts by weight of polybutylene terephthalate, 1-2 parts by weight of an antioxidant, 0.5-1 parts by weight of an ultraviolet stabilizer UV-328, 1-2 parts by weight of zinc stearate and 5-8 parts by weight of a curing accelerator DMP-30 in a mixer at 200-300 r / min for 3-5 minutes at a temperature of 70-90° C. to obtain a mixed resin; S6.2: Slowly add 2-3 parts by weight of light calcium carbonate and 4-5 parts by weight of modified phosphorus-containing layered nickel silicate to the mixed resin, stir at 800-1000r / min for 8-12min, and then feed 3-5 parts by weight of modified glass fiber into a twin-screw extruder through a special side feeding device at a uniform speed, with a screw speed of 250-350rpm and a temperature controlled at 230-280°C. After melt blending, extrusion and granulation, finished pellets are obtained, which is a composite material.

8. The composite material for the one-time molding of a photovoltaic support bridge without painting according to claim 7, characterized in that: The antioxidant in step S6.1 is antioxidant 1010.

9. The composite material for the one-time molding of a photovoltaic support bridge frame without painting according to claim 7, characterized in that: The ultraviolet stabilizer in step S6.1 is UV-328.

10. Use of the composite material according to any one of claims 1 to 9 in a one-time molding photovoltaic support bridge frame without painting.

Citation Information

Patent Citations

  • Multifunctional epoxy resin radical radiation protective compound material and preparation method thereof

    CN106317784A

  • Super-hydrophobic composite material taking fluorinated epoxy resin as matrix, and preparation method thereof, and super-hydrophobic surface

    CN111138938A

  • Core-shell particle for toughening thermosetting resin, composite material and preparation method

    CN116478536A

  • Naphthalene resin, epoxy resin and preparation method, composition and application thereof

    CN117946371A

  • Process for producing fluorinated methyl-benzyl alcohol

    US20040010167A1